Hamstring and Quadriceps Injuries in Athletes A Clinical Guide - Kaeding, Christopher C.; Borchers, James R. (Springer US : Imprint: Springer, 2014)
Injuries to the hamstring and quadriceps muscles can occur in both low- and high-impact sports and as such are among the more common injuries incurred by athletes. Reviewing the relevant physiology, epidemiology, mechanisms, clinical presentation and treatment of these conditions, Hamstring and Quadriceps Injuries in Athletes covers all sports-related injuries of the thigh musculature in one place. Topics covered include mid substance injuries, acute proximal tendon avulsions and harvesting of hamstrings, as well as strains, contusions and ruptures of the quadriceps, including the use of biologic enhancing agents in healing. Chapters on rehabilitation and injury prevention present techniques to maximize recovery and minimize long-term impairment, speeding up return to play. It will be an often-used and reliable guide for sports medicine practitioners, orthopedists, physical therapists, primary care physicians, team physicians and trainers who treat the injured athlete.